SENTIDOS TERRITORIAIS DA PROTEÇÃO SOCIAL NO LITORAL NORTE DA PARAÍBA - Emanuel Luiz Pereira da Silva (Universidade Federal do Maranhão, 2018)
The article starts from the reality of territorial studies within the northern coast of the state of Paraíba, this work consolidates the premise that, in general, we know there is no human society which has not developed some sort of social protection to their weakest members. We have opted for the Venn Diagram asour methodological tool, which allowed us to identify groups and their interrelations, carry out an exploratory search and also achieve a general overview on the intertwine of institutions, organizations and social groups. The 32 villages are connected by their life necessities and survival. They share a main cacique (the tribal chief) and have a local chief for each village.